L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Antibacterial cellulose acetate-based nanofiltration membrane through silver-assisted interfacial polymerization for efficient low-pressure desalination - Jian Zhang; Lianghui Zhong; Dongyang Han; Minfu Mo; Hui Zhang; Liulian Huang; Dong Wang (Journal of Water Process Engineering, 2026)

Study on emulsification property of chitosan with strong antibacterial activity - Junqing Qian; Junlan Yin; Peilong Ma; Chenghong Mo; Yan Chen; Hui Guo (Food Hydrocolloids, 2026)

Inhibition of protein-bound heterocyclic amines by citrus polymethoxyflavones via stabilizing myofibrillar protein conformation - Hui Xin; Diaodiao Yang; Shigang Liu; Lan Mo; Lei Zhou; Aihua Lou; Yan Liu; Qingwu Shen; Maomao Zeng; Jie Chen; Chaoyi Xue; Wei Quan; et al. (Food Chemistry, 2026)

Formation of HREE-enriched ion-adsorption ore from LREE-rich granodiorite: a case study from the Meng Khun deposit, Laos - Mingjun Xie; Jian Zhou; Xueqiu Wang; Huohua Mo; Hanliang Liu; Jinfeng Bai; Xuemiao Du; Hui Wu (Mineralium Deposita, 2026)

tRF-Glu-TTC-013 promotes colorectal cancer liver metastasis through a CREB3L1-AMDHD1 metabolic axis - Yuhui Li; Rongxi Chen; Hui Mo; Qi Wu; Zhun Li; Saiqi He; Aijun Zhou; Shuhui Yu; Chaohui Duan; Wen Ni; Jianming Li (Science Bulletin, 2026)

How water-saving irrigation enhances woody fruit quality via metabolic regulation - Yu Chen; Hui Geng; Yu-Chen Song; Dallin B. Kohler; Debatosh Das; Jian-Hua Zhang; Mo-Xian Chen; Fu-Yuan Zhu; Tao Song (Plant Science, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Insights into the role of pyrolysis temperature in cotransport of biochar nanoparticles and polystyrene nanoplastics in porous media - Xuanhao Lin; Ming Wu; Qusheng Li; Hui Li; Yanru Hao; Cehui Mo (Journal of Environmental Sciences, 2026)

Nanoplastics migration in hydroxyapatite-amended porous media: Integration of XDLVO theory and two-site kinetic modeling - Lulu Ding; Ming Wu; Qusheng Li; Hui Li; Cehui Mo (Journal of Contaminant Hydrology, 2026)

Molten salt − assisted graded carbonization tailors hard carbon pores toward enhanced sodium ions storage - Zuqin Duan; Rui Tang; Ying Mo; Peng Gao; Yan Duan; Hui Liu; Aiping Hu; Jilei Liu (Fuel, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

Interactive effects of forest succession and seasonal hydrology on heavy metal accumulation and ecological risk in subtropical forest soils - Wyckliffe Ayoma Ochieng; Brian Mwangi Njoroge; Vincent Ochieng Suba; Hui Mo; Emily Achieng Oluoch; Sohel Rana; Okechukwu Uzoma Iheme; Mengmeng Yang; Ekpoanwan Alfred Bassey; Ayesha Akter; Guowei Chu; Yuelin Li (Environmental Geochemistry and Health, 2026)

Toxicological effects of PM2.5-derived and PM2.5-relevant mixture of chlorinated paraffins on A549/THP-1 co-culture cells - Jing-Wen Huang; Chu Chu; Mo Yang; Henri Hakkarainen; Anna-Katharina Hensel; Nan-Xiang Jin; Marjut Roponen; Ari Leskinen; Mika Komppula; Dong Liang; Guang-Hui Dong; Pasi Jalava (Toxicology, 2026)

Multifunctional bacterial consortium degrading phthalates, promoting plant growth and inhibiting soil-borne pathogenic fungi - Jie-bin Zhou; Qiong-Wen Zhang; Yong-Ling Zhou; Hai-Feng Chen; Yu-Hong Huang; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2026)

Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Effective separation of organic species from a shale oil sludge - He-Qi Liu; Xian-Yong Wei; Zhi-Hao Ma; Jing Chen; Xiao-Yan He; Zhi-Min Zong; Xing Fan; Yu-Hong Kang; Fang-Jing Liu; Hai-Xu Zou; Guang-Hui Liu; Yierxiati Dilixiati; et al. (Journal of Environmental Management, 2026)

Highly thermally stable catalysts for VOCs oxidation: Synthesis, characterization and mechanisms - Yuchuan Ye; Jinhu Wang; Xinxin Zhang; Huisheng Fan; Hui Wang; Liuye Mo; Lei Jiao (Fuel, 2026)

Improving Kuroshio forecasts with an eddy-resolving AI prediction system - Junkai Qian; Qiang Wang; Wuhong Guo; Huier Mo; Hui Zhang (Ocean Modelling, 2026)

Amidoxime-modified PAN@Ce-UiO-66 nanocomposite fiber membrane for efficient removal of Cr(Ⅵ) from water - Yongzhang Qi; Hao Liang; Hebing Pei; Simin He; Hui Zhang; Shijing Li; Shikai Yu; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Linking microbial life history strategy to carbon use efficiency under changing substrate and nutrient conditions - Gang Huang; Yan-feng Cao; Meng-hui Dong; Mo Bahram; Yan-gui Su (CATENA, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Influence mechanism of attapulgite on the migration of carboxylated polystyrene nanoplastics and the role of environmental factors - Lulu Ding; Ming Wu; Hui Li; Yanru Hao; Qusheng Li; Cehui Mo (Journal of Contaminant Hydrology, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Contrasting influences of cloud properties and environmental factors on potential cloud precipitation capacity over China: A wet vs. dry years analysis - Pengguo Zhao; Wen Zhao; Shuying Mo; Xinyue Zhang; Hui Xiao; Yunjun Zhou; Zeneng He (Atmospheric Research, 2026)

Compositional convergence of dissolved organic matter from root litter to rhizosphere soil in a semiarid grassland of North China - Xiaohan Mo; Zongxiao Zhang; Mengke Wang; Qiang Zhang; Guodong Sun; Weifeng Hu; Guoping Chen; Deliang Kong; Chengcheng Dong; Hui Zeng; Junjian Wang (Organic Geochemistry, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Boosting H2 evolution via dual-functional interfacial design in Pt/Co0.85Se/g-C3N4 antenna photocatalyst - Xianglin Zhu; Jiangbo Wu; Xi Luo; Honghai Miao; Jinyuan Liu; Zhao Mo; Hui Xu; Shukui Shi; Xusheng Wang; Zhimin Yuan (Journal of Environmental Chemical Engineering, 2025)

Electron relay between S-Scheme heterojunction and variable-valence metals promotes photocatalytic hydrogen production over CeO2@MnXCd1-XS - Lei Yin; Qiuheng Wang; Jinyuan Zhang; Guanyu Wu; Jongkeun Lee; Peipei Sun; Zhao Mo; Hanxiang Chen; Xianglin Zhu; Hui Xu (Chemical Engineering Journal, 2025)

Ligninsulfonate composite hydrogel electrolyte for low-temperature resistant flexible supercapacitors - Peiyuan Zhang; Xuanhao Mo; Jing Li; Fengqing Zhi; Zhengwang Du; Hui Wu; Kai Liu; Lihui Chen; Xiaxing Zhou (Biomass and Bioenergy, 2025)

Synergistic effects of biochar and organic fertilizer on root exudates, microbial community, and yield in dry direct-seeded rice - Xiaoqiang Cao; Deping Liu; Jilong Liu; Lingling Zhang; Mo Li; Guoxin Shi; Hui Liu; Hao Wang; Weili Sun (Applied Soil Ecology, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Assessing the role of short-chain chlorinated paraffins in the toxicity of ambient particulate matter - Mo Yang; Chu Chu; Jing-Wen Huang; Guang-Hui Dong; Nan-Xiang Jin; Marjut Roponen; Pasi I. Jalava (Journal of Hazardous Materials, 2025)

Study on the role and function of RRS1 in cutaneous squamous cell carcinoma - Zhan-Yan Pan; Zhi-Nan Shi; Qiong Wu; Ting-Ting Hu; Xiao-Hui Mo; Da-Ke Dong; Qiang Ju (Tissue and Cell, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Co-transport behavior of aged polymeric methyl methacrylate nanoplastics and florfenicol antibiotic in porous media: Effects of electrolyte, pH, and aging duration - Lihui Tan; Ming Wu; Yanru Hao; Hui Li; Cehui Mo; Guoping Lu (Water Research, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Towards climate-adaptive equality in coastal megacities: Assessing urban flooding risk disparities and nonlinear effect of multidimensional indicators through an interpretable LightGBM-SHAP framework - Shiqi Zhou; Xiwen Geng; Weiyi Jia; Haowen Xu; Xiaodong Xu; Hui Chen; Mo Wang; Zhiqiang Wu (Sustainable Cities and Society, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Co-transport mechanism of polyethylene terephthalate nanoplastic and ibuprofen in porous media: Insights from column experiment and molecular dynamics simulation - Yiyan Cai; Ming Wu; Meng Chen; Yanru Hao; Hui Li; Cehui Mo (Journal of Environmental Chemical Engineering, 2025)

Degradation efficiency for phthalates and cooperative mechanism in synthetic bacterial consortium and its bioaugmentation for soil remediation - Huixiong Lü; Yu-Hong Huang; Qi-Fang Li; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai (Environmental Pollution, 2025)

Therapeutic effects of alkaline reduced water on type 2 diabetes mellitus induced by high-fat diet and streptozotocin in C57BL/6 mouse model - Hui Ma; Un Mo Jeong; Johny Bajgai; Md. Habibur Rahman; Chaodeng Mo; Wenjing He; Sofian Abdul-Nasir; Thu Thao Pham; Haiyang Zhang; Seong Hoon Goh; Bomi Kim; Hyeran Jung; et al. (Molecular & Cellular Toxicology, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

Surfactant-mediated transport of polyvinyl chloride nanoplastics in porous media: Influence of natural organic matter, natural inorganic ligands and electrolytes - Yujue Wang; Ming Wu; Yanru Hao; Hui Li; Cehui Mo (Journal of Contaminant Hydrology, 2025)

Long-term effects of PM2.5 constituents on childhood attention deficit hyperactivity disorder: evidence from a large population-based study in the Pearl River Delta Region, China - Hui-Xian Zeng; Wen-Jie Meng; Qing-Guo Zeng; Jing Wei; Lu-Sheng Liu; Qi-Zhen Wu; Bin Zhao; Anna Oudin; Mo Yang; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Deep blue OLEDs satisfying BT. 2020 standard enabled by a simple-structured multiple resonance emitter with CIEy coordinate of 0.02 - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Hui Wang; Tong-Yuan Zhang; Jia-Xiong Chen; Jia Yu; Kai Wang (Chemical Engineering Journal, 2025)

Landform basis for the rise of early cities in the upper Jialu river basin, central China - Ye Li; Peng Lu; Panpan Chen; Hui Wang; Shugang Yang; Xiangli Zhao; Yinan Liao; Yan Tian; Zhen Wang; Duowen Mo (Quaternary International, 2025)

Integrated metabolomic and transcriptomic insights into the role of anthocyanin and flavonoid biosynthesis in the pulp coloration mechanisms of Baccaurea ramiflora Lour. (Burmese grape) - Jianjian Huang; Jie Chen; Hui Zhu; Yuzhong Zheng; Xueying Wen; Suying Cai; Yingchun Zhu; Mo Ding; Qinghan Wu; Zikai Chen; Fengnian Wu (Plant Gene, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Sulfonamide-linked π-conjugated carbon nitride with enhanced intramolecular carrier generation and transfer for efficient photocatalysis - Jiajun Fu; Si Chen; Xuanhui Lin; Zongrui Li; Zhao Mo; Mingyue Dong; Zhigang Chen; Hui Xu (Journal of Environmental Chemical Engineering, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Insulin level regulators may affect cognitive ability caused by motion sickness: an experimental study - Mengyu Zhong; Jian Zhu; Bohan Zhang; Hui Shen; Hongxia Li; Yuxiao Tang; Shuang Nie; Fengfeng Mo (Metabolic Brain Disease, 2025)

Catalytic hydroconversion of oxydibenzene and benzyloxybenzene over NiCs/Al2O3 - Hong-Hui Gong; Xian-Yong Wei; Wen-Long Mo; Zhi-Min Zong; Guang-Hui Liu; Pei Liu; Kun-Peng Jiao (Fuel, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Macrophage membrane-based biomimetic nanocarrier system for enhanced immune activation and combination therapy in liver cancer - Wei Ni; Mingzhu Zhang; Yueni Mo; Wei Du; Hui Liu; Zhaosong Wang; Yanfen Cui; He Zhang; Zhiyong Wang; Liming Liu; Hui Guo; Ruifang Niu; et al. (Drug Delivery and Translational Research, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Circular RNA circ_0061183 regulates microglial polarization induced by airborne ultrafine particles in HMC3 cells via sponging miR-98-5p - Hui-Xian Zeng; Shuang-Jian Qin; Qi-Zhen Wu; Qing-Guo Zeng; Jia-Hui Li; Anna Oudin; Katja M. Kanninen; Mo Yang; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Electrospun 1D Al-LLZO incorporated PVDF-HFP composite electrolyte with fast Li+ pathway derived from highway-traction effect for high performance lithium metal batteries - Joo-Young Han; Sunghoon Kim; Dae Ung Park; Dongwoo Kang; Ji-Hui Oh; Da-Eun Hyun; Dong-Won Lee; Hwiyun Im; Jong-Min Oh; Sang-Mo Koo; Jeonghyun Kim; Jong Ho Won; et al. (Chemical Engineering Journal, 2025)

The trojan horse strategy in T-ALL therapy by engineering T-ALL-derived exosomes for targeted delivery of Isoliquiritigenin to the bone marrow to conquer Drug-Resistant T-ALL in PDX model - Yong Liu; Lindi Li; Cheng Ouyang; Zefan Du; Su Liu; Hailin Zou; Chunmou Li; Junbin Huang; Yucai Cheng; Mengyao Tian; Tianwen Li; Jiani Mo; et al. (Chemical Engineering Journal, 2025)

Ligand engineering boosts catalase-like activity of gold nanoclusters for cascade reactions combined with glucose oxidase in ZIF-8 matrix - Yi-Shu Wang; Chen Dong; Li Zou; Lin Zhao; Jian-Hua Qin; Hui-Lin Mo (Analytica Chimica Acta, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Hyperspectral classification of ancient cultural remains using machine learning - Rongji Luo; Peng Lu; Panpan Chen; Hongtao Wang; Xiaohu Zhang; Shugang Yang; Qingli Wei; Tao Wang; Yongqiang Li; Tao Liu; Deyang Jiang; Jun Du; et al. (Remote Sensing Applications: Society and Environment, 2025)

Investigating the environmental dynamics of emerging pollutants in response to global climate change: Insights from bibliometrics-based visualization analysis - Bogui Pan; Hong Tian; Boyou Pan; Ting Zhong; Miao Xin; Jinhua Ding; Junyu Wei; Hong-Jia Huang; Jing-Qian Tang; Fengtao Zhang; Nai-Xian Feng; Ce-Hui Mo (Science of The Total Environment, 2024)

Multi-scale correlation reveals the evolution of socio-natural contributions to tropospheric HCHO over China from 2005 to 2022 - Hui Xia; Dakang Wang; Gonzalo González Abad; Xiankun Yang; Lei Zhu; Dongchuan Pu; Xu Feng; Aoxing Zhang; Zhaolong Song; Yongru Mo; Jinnian Wang (Science of The Total Environment, 2024)

Polystyrene microplastics facilitate the chemical journey of phthalates through vegetable and aggravate phytotoxicity - Bogui Pan; Boyou Pan; Yiyuan Lu; Kunzheng Cai; Xiaoqiong Zhu; Li Huang; Lei Xiang; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

The interplay between prehistoric vegetation, climatic fluctuations and anthropogenic activities in Central China - Panpan Chen; Peng Lu; Yan Tian; Ye Li; Hui Wang; Jiaqiang Zhang; Xiangli Zhao; Duowen Mo (CATENA, 2024)

Desertibaculum subflavum gen. nov., sp. nov., a novel member of the family Sneathiellaceae isolated from the Kumtag Desert soil - Chu-Ying Feng; Huan-Huan He; Shuai Li; Zhuo-Huan Zheng; Yi-Jun Mo; Wen-Hui Lian; Chun-Yan Lu; Dong-Ya Zhang; Wen-Jun Li; Lei Dong (Antonie van Leeuwenhoek, 2024)

Pedobacter deserti sp. nov., a novel species isolated from desert soil - Jie Huang; Shuai Li; Ting-Ting She; Jun Liu; Yi-Jun Mo; Wen-Hui Lian; Dong-Ya Zhang; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Bioaccessibility and bioavailability of Pb and Cd in rice is affected by propolis and its extracts and Fe intervention - Ping Zhuang; Xianghua Chen; Shuo Sun; Yingwen Li; Hui Mo (Science of The Total Environment, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Ingenious regulation and activation of sites in the 2H-MoS2 basal planes by oxygen incorporation for enhanced photocatalytic hydrogen evolution of CdS - Guixin Zeng; Honghai Miao; Jiangbo Wu; Xianglin Zhu; Jianjian Yi; Xingwang Zhu; Haotian Qi; Zaiyong Jiang; Zhao Mo; Jinyuan Liu; Hui Xu (Chemical Engineering Journal, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Improving key gene expression and di-n-butyl phthalate (DBP) degrading ability in a novel Pseudochrobactrum sp. XF203 by ribosome engineering - Yunchang Xie; Nai-Xian Feng; Li Huang; Miaoer Wu; Cheng-Xuan Li; Fantao Zhang; Yunhong Huang; Quan-Ying Cai; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Enhanced tetracycline hydrochloride degradation at near neutral conditions with FeOx modified Bi4TaO8Cl catalyst: Coupling the photocatalytic and Fenton oxidation - Honghai Miao; Guixin Zeng; Huibin Zong; Zhao Mo; Xianglin Zhu; Dionysios D. Dionysiou; Hui Xu (Journal of Environmental Chemical Engineering, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Rufibacter psychrotolerans sp. nov., a Cold-Tolerating Novel Species Isolated from Desert Soil - Jun Liu; Shuai Li; Ting-Ting She; Jie Huang; Wen-Hui Lian; Yi-Jun Mo; Dong-Ya Zhang; Lei Dong; Wen-Jun Li (Current Microbiology, 2024)

Root-associated bacterial communities of vegetable Brassica parachinensis enrich pollutant-degrading taxa and functions for enhancing phthalate dissipation - Zhen Wang; Yu-Hong Huang; Minying He; Yan Hu; Xiaohan Xu; Quan-Ying Cai; Ce-Hui Mo; Huixiong Lü (Applied Soil Ecology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Biostimulation accelerates landfill stabilization and resource utilization efficiency, providing feasible technical support for the overall lifecycle management of landfills - Mingxing Li; Hui Jiang; Xiang Mo; Ruiding Li; Lifeng Liu; Wenchan Wu; Wendong Liu; Yong Xie; Xing Li; Fangfang Yan; Zhongping Qiu (Chemosphere, 2024)

The composition of the zebrafish intestinal microbial community varies under Bdellivibrio treatment from larvae to juveniles and adults - Haolin Mo; Qing Li; Qingsheng Cao; Haiyong Zhao; Lixin Wang; Hui Yang (Aquaculture, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Spatial variation, emissions, transport, and risk assessment of organophosphate esters in two large petrochemical complexes in southern China - Wen-Qing Mo; Zhen-Shan Huang; Qi-Qi Li; Jun Yao; Chun-You Zhu; Hui-Ying Guo; Yuan Zeng; She-Jun Chen (Journal of Environmental Management, 2024)

Simultaneous biodegradation of polycyclic aromatic hydrocarbons and phthalates by bacterial consortium and its bioremediation for complex polluted soil and sewage sludge - Yao-Si Chen; Yu-Hong Huang; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai (Bioresource Technology, 2024)

N/O co-doped carbon material supported Pd/Ni alloy for hydrodeoxygenation of biomass derivative - Guanhuan Mo; Wenjin Wu; Yiqian Luo; Maoling Pan; Wanqi Zhang; Hui Zhang; Kun Huang (Fuel, 2024)

Root-zone regulation and longitudinal translocation cause intervarietal differences for phthalates accumulation in vegetables - Bogui Pan; Xiaoqiong Zhu; Li Huang; Kunzheng Cai; Yan-Wen Li; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Chemosphere, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Relationship between precipitation and cloud properties in different regions of Southwest China - Yuting Wang; Pengguo Zhao; Chuanfeng Zhao; Hui Xiao; Shuying Mo; Liang Yuan; Chengqiang Wei; Yunjun Zhou (International Journal of Climatology, 2024)
The relationship between precipitation and cloud properties in Southwest China are investigated by using the CLARA‐A2 cloud parameters data and TRMM‐3B43 precipitation data from 1998 to 2015. Ice water path (IWP) and cloud top height (CTH) are significantly and positively correlated with precipitation in all regions, indicating that ice‐phase processes and cloud development processes are the critical processes influencing precipitation. Precipitation is also directly associated with cloud fractional coverage (CFC) due to the significant positive correlation between CFC and precipitation in all regions except the Sichuan Basin (SCB). A positive correlation between liquid water path (LWP) and precipitation is found in the Eastern Tibetan Plateau (ETP) and Yunnan‐Kweichow Plateau (YKP), but not in the Western Tibetan Plateau (WTP) and SCB. Notably, the response of precipitation to LWP is not as good as that to IWP in SCB. Precipitation is significantly negatively correlated with ice effective radius (IREF) in WTP and ETP and positively correlated with liquid effective radius (LREF) in ETP, YKP and SCB. IREF and LREF are closely related to cloud microphysical processes. Specifically, small IREF could accelerate the Bergeron process and thus increase precipitation, while large LREF is closely related to the cloud droplets coalescence process. Results indicate that the difference in precipitation between the cold and warm seasons is related to convective available potential energy (CAPE) and low troposphere relative humidity (RH). High CAPE and RH favour the precipitation occurrence in Southwest China. The influence of CAPE and RH on precipitation is more significant in the ETP than that in the WTP, owing to the orographic lifting and moisture transport from the Indian Ocean. Thermodynamic and humidity conditions have a greater impact on precipitation by influencing LREF, LWP and IWP in YKP. In SCB, precipitation shows a strong dependence on CAPE, IWP and LREF, but not on RH.

Developing cellulose-based hydrophobic/hydrophilic composites for efficient adsorption of oils and heavy metals from water - Fengqin Yin; Dianli Zhou; Yeling Mo; Junjie Zhu; Yunyan Zhang; Hui Cao; Min Yuan; Tai Ye; Fei Xu (Science of The Total Environment, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Iron complex regulated synergistic effect between the current and peroxymonosulfate enhanced ultrafast oxidation of perfluorooctanoic acid via free radical dominant electrochemical reaction - Meng Li; Peitong Cen; Lei Huang; Jia Yan; Shaoqi Zhou; King Lun Yeung; Ce-Hui Mo; Hongguo Zhang (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Climatic precipitation efficiency and its dependence on environmental factors over the Sichuan Basin and adjacent regions, Southwest China - Shuying Mo; Pengguo Zhao; Chuanfeng Zhao; Hui Xiao; Yuting Wang; Peiwen Zhang; Xiaohang Wen; Shuang Qiu (Theoretical and Applied Climatology, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Fostering green economic growth through sustainable management of natural resources - Zerong Li; Lan Li; Mo Hui (Resources Policy, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

A new understanding on the prerequisite of antibiotic biodegradation in wastewater treatment: Adhesive behavior between antibiotic-degrading bacteria and ciprofloxacin - Sining Zhou; Yanyan Jia; Heting Fang; Chao Jin; Yijun Mo; Zihan Xiao; Ning Zhang; Lianpeng Sun; Hui Lu (Water Research, 2024)

Root-associated bacteria strengthen their community stability against disturbance of antibiotics on structure and functions - Yu-Hong Huang; Yu-Jie Yang; Jie-Yu Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2024)

Retraction Note: Two Metal Complexes: Selective Detection of Fe3 + Ion and Promotion Activity on Mesenchymal Stem Cells Differentiate into Vascular Endothelial Cells - Qin-Ming Zhao; Zhong-You Xu; Hui-Peng Zhu; Yu-Xiang He; Mo Wang (Journal of Fluorescence, 2024)

Performance and mechanism of biochar@FeMg-LDH for efficient activation of persulfate for degradation of 2, 4-dichlorophenol in groundwater - Yuanye Mo; Xianrong Meng; Chengbao Liu; Wei Xu; Leizhi Zheng; Feng Chen; Junchao Qian; Hui Cai; Zhigang Chen (Environmental Science and Pollution Research, 2024)

Response and adaptation of rhizosphere microbiome to organic pollutants with enriching pollutant-degraders and genes for bioremediation: A critical review - Huixiong Lü; Guang-Xuan Tang; Yu-Hong Huang; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Hui Li; Quan-Ying Cai; Qing X. Li (Science of The Total Environment, 2024)

Insights into the molecular network underlying phytotoxicity and phytoaccumulation of ciprofloxacin - Hai-Ming Zhao; He-Biao Huang; Zhen-Xuan Zhan; Yao-Yao Ye; Ji-Liang Cheng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Yunchang Xie; Ce-Hui Mo (Science of The Total Environment, 2024)

Structure-activity relationship study of high entropy oxides catalysts for oxygen evolution reaction - Yuanxia Lao; Xiaoqing Huang; Leping Liu; Xiangli Mo; Jiali Huang; Yating Qin; Qianqian Mo; Xinfeng Hui; Zheng Yang; Wei Jiang (Chemical Engineering Journal, 2024)

Benefit evaluation of in-situ Cd immobilization with naturally occurring minerals using an analytical hierarchy process - Fangman Chen; Peng Mao; Mimi Wang; Yingwen Li; Yongxing Li; Kuaifei Xia; Jiantong Chen; Hui Mo; Faming Wang; Zhian Li; Ping Zhuang (Chemosphere, 2024)

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Basin-scale reconstruction of late Pleistocene-Holocene fluvial landform evolution and its mechanisms in transitional areas between Taihang Mountain and North China Plain - Yan Tian; Panpan Chen; Peng Lu; Ye Li; Hui Wang; Liang Zhou; Xiaohu Zhang; Shugang Yang; Xingguo Zhang; Xiaoyu Chai; Haiguo Zhai; Min Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Cyano-rich carbon nitride with tunable n → π* electronic transition for enhanced broad-spectrum photocatalytic H2O2 production - Peipei Sun; Zhao Mo; Jinyuan Zhang; Guanyu Wu; Zhihuan Miao; Kang Zhong; Yuechang Wei; Chunman Jia; Zhigang Chen; Hui Xu (Chemical Engineering Journal, 2023)

Developing positively surface-charged carbon dots as “semiconductor electrolyte” for photo-electrochemical H2O2 production based on oxygen reduction - Yong-Shuai Zhang; Hui-Min Duan; Na Wang; Dong-Dong Wei; Liu-Meng Mo; Ning Wang; Xin-Pei Wang; Shuang-Lei Lei; Yuan Zhang; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Metabolomic Analysis of Fermented Tibetan Tea Using Bacillus circulans and Their Biological Activity on Mice via the Intestine–Hepatic Axis - Ning Wang; Shan Mo; Tao Wu; Muhammad Aamer Mehmood; Haiyan Sun; Yongqing Tang; Jie Mei; Yuan Mei; Wen Fang; Xiongjun Xiao; Hui Zhu (Probiotics and Antimicrobial Proteins, 2023)

Rapid detection of foodborne pathogens in diverse foodstuffs by universal electrochemical aptasensor based on UiO-66 and methylene blue composites - Ge Dai; Handong Yao; Liuhong Yang; Yifeng Ding; Shuxin Du; Hui Shen; Fengfeng Mo (Food Chemistry, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Resource allocation theory reveals sulfur shortage for microbes under phosphorus amendment in tropical forests with divergent land use history - Cong Wang; Qinggong Mao; Taiki Mori; Juan Huang; Hui Mo; Jiangming Mo; Xiankai Lu (Soil Biology and Biochemistry, 2023)

Development of Au8 nanocluster-based fluorescent strip immunosensor for sensitive detection of aflatoxin B1 - Zi-Hui Shao; Aoqiang Zhai; Yue Hua; Hui-Lin Mo; Fuwei Xie; Xueli Zhao; Ge Zhao; Shuang-Quan Zang (Analytica Chimica Acta, 2023)

Omics integration for in-depth understanding of the low-carbon co-culture platform system of Chlorella vulgaris-Escherichia coli - Hui Liu; Mo Xian; Yujin Cao; Jing Guo; Lijun Kan; Xin Xu (Algal Research, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Assembly of understory woody communities during the close-to-nature restoration of a Pinus massoniana lamb. plantation in the southern subtropical region of China: From environmental filtering to competitive exclusion - Liuxin Huang; Xiaomei Pan; Jiangming Ma; Rui Jian; Hui Zhang; Kundong Bai; Yanhua Mo; Qiwei Zhang; Zhangqi Yang (Forest Ecology and Management, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

The Mechanism of Immobilization of Cd(II) by Phosphate-Solubilizing Bacteria Bacillus sp. B19 - Si-Yi Liu; Qiang Pu; Tian-Jin Mo; Guixiang Peng; Yan Sun; Yulong Zhang; Jinjin Wang; Yongtao Li; Hui-Juan Xu (Water, Air, & Soil Pollution, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

An ultra-sensitive and selective electrochemical sensor based on GOCS composite and ion imprinted polymer for the rapid detection of Cd2+ in food samples - Fengqin Yin; Yeling Mo; Xueting Liu; Hongzhi Yang; Dianli Zhou; Hui Cao; Tai Ye; Fei Xu (Food Chemistry, 2023)

Occurrence, risk, and treatment of ciprofloxacin and clarithromycin in drainage - Meng Li; Dengyu Ji; Malvin Subroto Pamudji; Ka Hei Lui; Yayi Zhao; Gaoshen Zhao; Shao-Qi Zhou; Ce-Hui Mo; Wei Han; King Lun Yeung (Chemical Engineering Journal, 2023)

Chalcopyrite-activated sodium percarbonate oxidation for sludge dewaterability enhancement: Synergetic roles of •OH and 1O2 - Jialin Liang; Zexing Tan; Lei Zhang; Chengjian Li; Zhihua Mo; Maoyou Ye; Jing Ai; Shaosong Huang; Shuiyu Sun; Hui Liu (Chemical Engineering Journal, 2023)

Changes of spring wind erosion based on wind erosion climate factor in the black soil region of Northeast China - Ping Yan; Sheng-tai Ji; Xiu-fen Li; Hai-xia Zhu; Liang-liang Wang; Mo Zhai; Ping Wang; Hui-ying Zhao (Journal of Mountain Science, 2023)

Neiella litorisoli sp. nov., an alginate lyase: producing bacterium from South China Sea, and proposal of Echinimonadaceae fam. nov. in the order Alteromonadales - Jing-Ran Sun; Kun-Lian Mo; Xue Li; Yong-Hua Hu; Zhi-Yuan Liu; Hui-Qin Huang (Archives of Microbiology, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Conversion of biomass-derived monosaccharide into furfural over Cr–Mg-LDO@bagasse catalysts - Shuang-Lan Hu; Shan Liang; Liu-Zhen Mo; Hui-Hui Su; Jun-Sheng Huang; Ping-Jun Zhang; Jian-Nan Qin (Sustainable Chemistry and Pharmacy, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Endophytic Phthalate-degrading Bacillus subtilis N-1-gfp colonizing in soil-crop system shifted indigenous bacterial community to remove di-n-butyl phthalate - Li-Hui Liu; Jia-Yan Zhang; Guang-Xuan Tang; Yu-Hong Huang; Xiang-Qing Xie; Jun Geng; Hui-Xiong Lü; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Prehistoric damaging earthquake promoted the decline of “Heluo Ancient State” in Early China - Xiu Hu; Peng Lu; Youli Li; Duowen Mo; Wanfa Gu; Qingri Liu; Ailun Guo; Panpan Chen; Hui Wang; Yan Tian; Xu Wang; Yayi Hu; et al. (Science China Earth Sciences, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Three coordinate nitrogen (N3c) vacancies from in-situ hydrogen bond breaking over polymeric carbon nitride for efficient photocatalysis - Jiajun Fu; Zhao Mo; Hanxiang Chen; Zhigang Chen; Xianglin Zhu; Jia Yan; Jinyuan Liu; Yuechang Wei; Huaming Li; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

How the Wild Sugarcane Resource Miscanthus floridulus Responds to Low-Temperature Stress: A Physiological and Transcriptomic Analysis - Hong-Li Yang; Zhi-Jun Guo; Lu Jiang; Jun-Jun He; Qing Liu; Mo Chen; Xing-Hua Yu; Xian-Hong Wang; Qing-Hui Yang (Sugar Tech, 2023)

Elevated ozone enhances the network stability of rhizospheric bacteria rather than fungi - Zhengsheng Yu; Xin Chen; Feng Hua Zhai; Qun Gao; Xun Wen Chen; Xue Guo; Yansen Xu; Meng Ying Gao; Cehui Mo; Zhaozhong Feng; Yunfeng Yang; Hui Li (Agriculture, Ecosystems & Environment, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Genome mining-guided activation of two silenced tandem genes in Raoultella ornithinolytica XF201 for complete biodegradation of phthalate acid esters - Nai-Xian Feng; Fei Zhang; Yunchang Xie; Hui Bin; Lei Xiang; Yan-Wen Li; Fantao Zhang; Yunhong Huang; Hai-Ming Zhao; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Science of The Total Environment, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Microbiological analysis and characterization of Salmonella and ciprofloxacin-resistant Escherichia coli isolates recovered from retail fresh vegetables in Shaanxi Province, China - Chenyang Cao; Wenxing Zhao; Zexun Lü; Yixin Mo; Wei Hu; Shengyuan Sun; Huabin Cheng; Jiaqi Ma; Sirui Xiong; Xiaorong Jin; Hui Yang; Li Bai; et al. (International Journal of Food Microbiology, 2023)

Iron-rich sludge biochar triggers sodium percarbonate activation for robust sulfamethoxazole removal: Collaborative roles of reactive oxygen species and electron transfer - Zhihua Mo; Zexing Tan; Jialin Liang; Zhijie Guan; Xiaojian Liao; Jianxiong Jian; Hui Liu; Yihong Li; Wencan Dai; Shuiyu Sun (Chemical Engineering Journal, 2023)

Weavable, large-scaled, rapid response, long-term stable electrochemical fabric sensor integrated into clothing for monitoring potassium ions in sweat - Lili Mo; Xiangda Ma; Longfei Fan; John H. Xin; Hui Yu (Chemical Engineering Journal, 2023)

Terpenoids from the roots of Chloranthus henryi Hemsl. var. hupehensis (Pamp.) K. F. Wu and their chemotaxonomic significance - Shuai Liu; Zi-Mo Zhang; Hui Yang; Yun-He Zou; Ning Wang; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

Effect of solvent swelling with different enhancement methods on the microstructure and pyrolysis performance of Hefeng subbituminous coal - Hui Kan; Yue Wang; Wen-Long Mo; Xian-Yong Wei; Hong-Yu Mi; Kong-Jun Ma; Mei-Xia Zhu; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Xing Fan (Fuel, 2023)

Highly exposed active sites of Au nanoclusters for photocatalytic CO2 reduction - Jianfeng Tian; Kang Zhong; Xingwang Zhu; Jinman Yang; Zhao Mo; Jinyuan Liu; Jiachao Dai; Yuanbin She; Yanhua Song; Huaming Li; Hui Xu (Chemical Engineering Journal, 2023)

Sargassum horneri Extract Alleviates Testosterone-Induced Benign Prostatic Hyperplasia In vitro and In vivo - Yae-Ji Kim; Kyung-Hyun Kim; Hyun-Yong Kim; Sung-Mo Kang; Geum-Lan Hong; Hui-Ju Lee; Soon-Sung Lim; Ju-Young Jung (Journal of Aquatic Food Product Technology, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

DESA: a novel hybrid decomposing-ensemble and spatiotemporal attention model for PM2.5 forecasting - Shuwei Fang; Qi Li; Hamed Karimian; Hui Liu; Yuqin Mo (Environmental Science and Pollution Research, 2022)

Selection of Payloads for Antibody–Drug Conjugates Targeting Ubiquitously Expressed Tumor-Associated Antigens: a Case Study - Bing Yao; Xiao Gao; Mo Dan; Can Yuan; Xixin Hu; Zhaopeng Sun; Xiwu Hui; Boning Liu; Pingkai Ouyang; Guoguang Chen (The AAPS Journal, 2022)

Comprehensive analysis of TCR repertoire of COVID-19 patients in different infected stage - Guangyu Wang; Yongsi Wang; Shaofeng Jiang; Wentao Fan; Chune Mo; Weiwei Gong; Hui Chen; Dan He; Jinqing Huang; Minglin Ou; Xianliang Hou (Genes & Genomics, 2022)

The level of endogenous JA is critical for activation of SA- and JA-defensive signaling pathway in japonica rice cultivar Ziyu44 upon Magnaporthe oryzae infection - Xingyu An; Hui Zhang; Jinlu Li; Rui Yang; Qianchun Zeng; Mo Wang; Qiong Luo (Journal of Plant Pathology, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Characteristics of typical air pollutants in a valley-basin city in South China - Chu Wu; Jibing Li; Xiaoping Lin; Yangzhi Mo; Hui Zhang; Zhihui Liao; Yu Wang; Duohong Chen (Meteorology and Atmospheric Physics, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

Revitalization plans for mountain ecological villages in South Korea - Hag-mo Kang; Soo-im Choi; So-hui Jeon; Chong-kyu Lee; Hyun Kim (Environment, Development and Sustainability, 2021)

RETRACTED ARTICLE: Two Metal Complexes: Selective Detection of Fe3+ Ion and Promotion Activity on Mesenchymal Stem Cells Differentiate Into Vascular Endothelial Cells - Qin-Ming Zhao; Zhong-You Xu; Hui-Peng Zhu; Yu-Xiang He; Mo Wang (Journal of Fluorescence, 2021)

Proteomic Analysis of Serum Differentially Expressed Proteins Between Allergic Bronchopulmonary Aspergillosis and Asthma - Hui Cai; Diquan Shuai; Xiaomin Xue; Yuqing Mo; Xixi Song; Ling Ye; Shuiming Li; Daiwei Wang; Yun Wang; Meiling Jin (Mycopathologia, 2021)

High-Level Expression and Purification of Melittin in Escherichia coli Using SUMO Fusion Partner - Qiu-chi Chen; Lei Liu; Tian-Yi Yu; Lu Tang; Mo-li Yin; Wen-he Zhu; Xiu-yun Jiang; Hui-yan Wang (International Journal of Peptide Research and Therapeutics, 2021)

Preliminary report on the improved resistance towards Pseudomonas syringae pv. actinidiae of cultivated kiwifruit (Actinidia chinensis) when grafted onto wild Actinidia guilinensis rootstock in vitro - Fa-ming Wang; Jie-wei Li; Kai-yu Ye; Hong-juan Gong; Ping-ping Liu; Qiao-sheng Jiang; Bei-bei Qi; Quan-hui Mo (Journal of Plant Pathology, 2021)

EDTAD-modified cassava stalks loaded with Fe3O4: highly efficient removal of Pb2+ and Zn2+ from aqueous solution - Caiyan Kang; Qiuyan Li; Hui Yi; Hua Deng; Weiming Mo; Mianwu Meng; Siyu Huang (Environmental Science and Pollution Research, 2021)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Effects of arbuscular mycorrhizal fungi on redox homeostasis of rice under Cd stress - Hui Li; Xun Wen Chen; Li Wu; Na Luo; Wei Xiong Huang; Ce Hui Mo; Yan Wen Li; Lei Xiang; Hai Ming Zhao; Quan Ying Cai; Ming Hung Wong (Plant and Soil, 2020)

Global response patterns of plant photosynthesis to nitrogen addition: A meta‐analysis - Xingyun Liang; Tong Zhang; Xiankai Lu; David S. Ellsworth; Hormoz BassiriRad; Chengming You; Dong Wang; Pengcheng He; Qi Deng; Hui Liu; Jiangming Mo; Qing Ye (Global Change Biology, 2020)
A mechanistic understanding of plant photosynthetic response is needed to reliably predict changes in terrestrial carbon (C) gain under conditions of chronically elevated atmospheric nitrogen (N) deposition. Here, using 2,683 observations from 240 journal articles, we conducted a global meta‐analysis to reveal effects of N addition on 14 photosynthesis‐related traits and affecting moderators. We found that across 320 terrestrial plant species, leaf N was enhanced comparably on mass basis ( N mass , +18.4%) and area basis ( N area , +14.3%), with no changes in specific leaf area or leaf mass per area. Total leaf area (TLA) was increased significantly, as indicated by the increases in total leaf biomass (+46.5%), leaf area per plant (+29.7%), and leaf area index (LAI, +24.4%). To a lesser extent than for TLA, N addition significantly enhanced leaf photosynthetic rate per area ( A area , +12.6%), stomatal conductance ( g s , +7.5%), and transpiration rate ( E , +10.5%). The responses of A area were positively related with that of g s , with no changes in instantaneous water‐use efficiency and only slight increases in long‐term water‐use efficiency (+2.5%) inferred from 13 C composition. The responses of traits depended on biological, experimental, and environmental moderators. As experimental duration and N load increased, the responses of LAI and A area diminished while that of E increased significantly. The observed patterns of increases in both TLA and E indicate that N deposition will increase the amount of water used by plants. Taken together, N deposition will enhance gross photosynthetic C gain of the terrestrial plants while increasing their water loss to the atmosphere, but the effects on C gain might diminish over time and that on plant water use would be amplified if N deposition persists.

Long-term phosphorus addition downregulates microbial investments on enzyme productions in a mature tropical forest - Cong Wang; Taiki Mori; Qinggong Mao; Kaijun Zhou; Zhuohang Wang; Yongqun Zhang; Hui Mo; Xiankai Lu; Jiangming Mo (Journal of Soils and Sediments, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Ginsenoside compound K ameliorates Alzheimer’s disease in HT22 cells by adjusting energy metabolism - Xijun Chen; Hui Li; Qing Yang; Xingcheng Lan; Jifeng Wang; Zhanhong Cao; Xiaozheng Shi; Jing Li; Mo Kan; Xiaobo Qu; Na Li (Molecular Biology Reports, 2019)

Fine root dynamics responses to nitrogen addition depend on root order, soil layer, and experimental duration in a subtropical forest - Wenjuan Wang; Qifeng Mo; Xiaoge Han; Dafeng Hui; Weijun Shen (Biology and Fertility of Soils, 2019)

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

Correction to: Expression and Function of Zinc-α2-Glycoprotein - Xin Wei; Xi Liu; Changhong Tan; Lijuan Mo; Hui Wang; Xi Peng; Fen Deng; Lifen Chen (Neuroscience Bulletin, 2019)

Expression and Function of Zinc-α2-Glycoprotein - Xin Wei; Xi Liu; Changhong Tan; Lijuan Mo; Hui Wang; Xi Peng; Fen Deng; Lifeng Chen (Neuroscience Bulletin, 2019)

Geochronology, geochemistry and Sr-Nd-Pb-Hf isotopes of the Early Paleogene gabbro and granite from Central Lhasa, southern Tibet: petrogenesis and tectonic implications - Yun-hui Zhang; Hua-wen Cao; Steven P. Hollis; Li Tang; Mo Xu; Jun-sheng Jiang; Shun-bao Gao; Yang-shuang Wang (International Geology Review, 2019)

Identification of Differentially Expressed Genes of Rice Under Cadmium Stress Using DDRT-PCR Approach - Jian-hui Wang; Hai-Ming Zhao; Ce-hui Mo; Xue-wen Hou (Bulletin of Environmental Contamination and Toxicology, 2019)

Hierarchical Flood Operation Rules Optimization Using Multi-Objective Cultured Evolutionary Algorithm Based on Decomposition - Yongqi Liu; Hui Qin; Li Mo; Yongqiang Wang; Duan Chen; Shusen Pang; Xingli Yin (Water Resources Management, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Global development and trend of wind tunnel research from 1991 to 2014: a bibliometric analysis - Ziwei Mo; Hui-Zhen Fu; Yuh-Shan Ho (Environmental Science and Pollution Research, 2018)

The triggering receptor expressed by myeloid cells-1 activates TLR4-MyD88-NF-κB-dependent signaling to aggravate ventilation-induced lung inflammation and injury in mice - Xiaoxia Wang; Bijun Luo; Yanyan Lu; Dengge Pang; Jianqiu Zheng; Jianlan Mo; Hui Huang; Jifeng Feng (Cell and Tissue Research, 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Highly cited articles in wind tunnel-related research: a bibliometric analysis - Ziwei Mo; Hui-Zhen Fu; Yuh-Shan Ho (Environmental Science and Pollution Research, 2018)

Toxicological effects of microcystin-LR on earthworm (Eisenia fetida) in soil - Hong-Fei Wen; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Lei Chen; Quan-Ying Cai; Hui Li; Ce-Hui Mo; Dong-Mei Zhou; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Variation in accumulation and translocation of di-n-butyl phthalate (DBP) among rice (Oryza sativa L.) genotypes and selection of cultivars for low DBP exposure - Quan-Ying Cai; Pei-Yun Xiao; Hai-Ming Zhao; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Hui Li; Lei Xiang; Ce-Hui Mo (Environmental Science and Pollution Research, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Oral bioaccessibility and human exposure assessment of cadmium and lead in market vegetables in the Pearl River Delta, South China - Ping Zhuang; Yingwen Li; Bi Zou; Feng Su; Chaosheng Zhang; Hui Mo; Zhian Li (Environmental Science and Pollution Research, 2016)

Occurrence and risk assessment of tetracycline antibiotics in soil from organic vegetable farms in a subtropical city, south China - Lei Xiang; Xiao-Lian Wu; Yuan-Neng Jiang; Qing-Yun Yan; Yan-Wen Li; Xian-Pei Huang; Quan-Ying Cai; Ce-Hui Mo (Environmental Science and Pollution Research, 2016)

Chloride ion-driven transformation from Ag3PO4 to AgCl on the hydroxyapatite support and its dual antibacterial effect against Escherichia coli under visible light irradiation - Xiaoting Hong; Min Li; Shengdao Shan; K. S. Hui; Mingyue Mo; Xiaoli Yuan (Environmental Science and Pollution Research, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Cotton S-adenosylmethionine decarboxylase-mediated spermine biosynthesis is required for salicylic acid- and leucine-correlated signaling in the defense response to Verticillium dahliae - Hui-Juan Mo; Yan-Xiang Sun; Xiao-Li Zhu; Xing-Fen Wang; Yan Zhang; Jun Yang; Gui-Jun Yan; Zhi-Ying Ma (Planta, 2016)

Biodegradation of di-n-butylphthalate and phthalic acid by a novel Providencia sp. 2D and its stimulation in a compost-amended soil - Hai-Ming Zhao; Huan Du; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo (Biology and Fertility of Soils, 2016)

Sequential dynamic artificial neural network modeling of a full-scale coking wastewater treatment plant with fluidized bed reactors - Hua-Se Ou; Chao-Hai Wei; Hai-Zhen Wu; Ce-Hui Mo; Bao-Yan He (Environmental Science and Pollution Research, 2015)

Effects of the size and morphology of zinc oxide nanoparticles on the germination of Chinese cabbage seeds - Lei Xiang; Hai-Ming Zhao; Yan-Wen Li; Xian-Pei Huang; Xiao-Lian Wu; Teng Zhai; Yue Yuan; Quan-Ying Cai; Ce-Hui Mo (Environmental Science and Pollution Research, 2015)

Association of IgE-mediated allergen sensitivity and promoter polymorphisms of chemokine (C–C motif) ligand 5 gene in Han Chinese patients with allergic skin diseases - Ji-Chang Zhou; Yu-mei Zhu; Zheng Chen; Shan He; Shi-jie Zheng; Jun-luan Mo; Xiao-li Liu; Chun-mei Gong; Bin Hou; Hui Yang (Genes & Genomics, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Environmental mercury concentrations in cultured low-trophic-level fish using food waste-based diets - Zhang Cheng; Wing Yin Mo; Yu Bon Man; Cheung Lung Lam; Wai Ming Choi; Xiang Ping Nie; Yi Hui Liu; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Climate warming-induced upward shift of Moso bamboo population on Tianmu Mountain, China - Xin-zhang Song; Chang-hui Peng; Guo-mo Zhou; Hong Jiang; Wei-feng Wang; Wen-hua Xiang (Journal of Mountain Science, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Association of RANTES and MBL gene polymorphisms with systemic lupus erythematosus: a meta-analysis - Wang-Dong Xu; Hui Peng; Mo Zhou; Min Zhang; Bao-Zhu Li; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2013)

Heavy metal contamination of urban soils and dusts in Guangzhou, South China - Quan-Ying Cai; Ce-Hui Mo; Hai-Qin Li; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Xiao-Lian Wu (Environmental Monitoring and Assessment, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Metal (Pb, Cd, and Cu)-induced reactive oxygen species accumulations in aerial root cells of the Chinese banyan (Ficus microcarpa) - Nan Liu; Zhifang Lin; Hui Mo (Ecotoxicology, 2012)

Occurrence of Nonylphenol and Nonylphenol Monoethoxylate in Soil and Vegetables from Vegetable Farms in the Pearl River Delta, South China - Quan-Ying Cai; Hui-Juan Huang; Huixiong Lü; Ce-Hui Mo; Jun Zhang; Qiao-Yun Zeng; Jun-Jian Tian; Yan-Wen Li; Xiao-Lian Wu (Archives of Environmental Contamination and Toxicology, 2012)

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia - Yao-Chun Hsu; Han-Mo Chiu; Jyh-Ming Liou; Chun-Chao Chang; Jaw-Town Lin; Hui-Hsiung Liu; Ming-Shiang Wu (Cancer Causes & Control, 2012)

Intranasal immunization with autolysin (LytA) in mice model induced protection against five prevalent Streptococcus pneumoniae serotypes in China - Zhu Qing Yuan; Zhi Yue Lv; Hui Quan Gan; Mo Xian; Kou Xing Zhang; Jing Ying Mai; Xin Bing Yu; Zhong Dao Wu (Immunologic Research, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

Production of triploid plants of papaya by endosperm culture - De-Quan Sun; Xin-Hua Lu; Guo-Lu Liang; Qi-Gao Guo; Yi-Wei Mo; Jiang-Hui Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Soil-atmosphere exchange of greenhouse gases in subtropical plantations of indigenous tree species - Hui Wang; Shirong Liu; Jiangming Mo; Tao Zhang (Plant and Soil, 2010)

Correlation between leaf litter and fine root decomposition among subtropical tree species - Hui Wang; Shirong Liu; Jiangming Mo (Plant and Soil, 2010)

Cumulative effects of nitrogen additions on litter decomposition in three tropical forests in southern China - Hua Fang; Jiangming Mo; Shaolin Peng; Zhian Li; Hui Wang (Plant and Soil, 2009)

Polycyclic Aromatic Hydrocarbons and Phthalic Acid Esters in Vegetables from Nine Farms of the Pearl River Delta, South China - Ce-Hui Mo; Quan-Ying Cai; Shi-Rong Tang; Qiao-Yun Zeng; Qi-Tang Wu (Archives of Environmental Contamination and Toxicology, 2009)

Singularly perturbed solution of coupled model in atmosphere-ocean for global climate - Jiaqi Mo; Wantao Lin; Hui Wang (Chinese Geographical Science, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Emissions of nitrous oxide from three tropical forests in Southern China in response to simulated nitrogen deposition - Wei Zhang; Jiangming Mo; Guirui Yu; Yunting Fang; Dejun Li; Xiankai Lu; Hui Wang (Plant and Soil, 2008)

Nitrogen addition reduces soil respiration in a mature tropical forest in southern China - JIANGMING MO; WEI ZHANG; WEIXING ZHU; PER GUNDERSEN; YUNTING FANG; DEJUN LI; HUI WANG (Global Change Biology, 2008)
Response of soil respiration (CO 2 emission) to simulated nitrogen (N) deposition in a mature tropical forest in southern China was studied from October 2005 to September 2006. The objective was to test the hypothesis that N addition would reduce soil respiration in N saturated tropical forests. Static chamber and gas chromatography techniques were used to quantify the soil respiration, following four‐levels of N treatments (Control, no N addition; Low‐N, 5 g N m −2 yr −1 ; Medium‐N, 10 g N m −2 yr −1 ; and High‐N, 15 g N m −2 yr −1 experimental inputs), which had been applied for 26 months before and continued throughout the respiration measurement period. Results showed that soil respiration exhibited a strong seasonal pattern, with the highest rates found in the warm and wet growing season (April–September) and the lowest rates in the dry dormant season (December–February). Soil respiration rates showed a significant positive exponential relationship with soil temperature, whereas soil moisture only affect soil respiration at dry conditions in the dormant season. Annual accumulative soil respiration was 601±30 g CO 2 ‐C m −2 yr −1 in the Controls. Annual mean soil respiration rate in the Control, Low‐N and Medium‐N treatments (69±3, 72±3 and 63±1 mg CO 2 ‐C m −2 h −1 , respectively) did not differ significantly, whereas it was 14% lower in the High‐N treatment (58±3 mg CO 2 ‐C m −2 h −1 ) compared with the Control treatment, also the temperature sensitivity of respiration, Q 10 was reduced from 2.6 in the Control with 2.2 in the High‐N treatment. The decrease in soil respiration occurred in the warm and wet growing season and were correlated with a decrease in soil microbial activities and in fine root biomass in the N‐treated plots. Our results suggest that response of soil respiration to atmospheric N deposition in tropical forests is a decline, but it may vary depending on the rate of N deposition.

Cumulative effects of nitrogen additions on litter decomposition in three tropical forests in southern China - Hua Fang; Jiangming Mo; Shaolin Peng; Zhian Li; Hui Wang (Plant and Soil, 2007)

The salt stress relief and growth promotion effect of Rs-5 on cotton - Haitao Yue; Wenping Mo; Chun Li; Yuanyuan Zheng; Hui Li (Plant and Soil, 2007)

Expressions of polypeptide: N-acetylgalactosaminyltransferase in leukemia cell lines during 1,25-dihydroxyvitamin D3 induced differentiation - Hao Qiu; Xiang-Hong Guo; Jian-Hua Mo; Mei-Fang Jin; Shi-Liang Wu; Hui-Li Chen (Glycoconjugate Journal, 2006)

Variational iteration solving method for sea-air oscillator model of interdecadal climate fluctuations - Jia-qi Mo; Yi-hua Lin; Hui Wang (Chinese Geographical Science, 2005)